Standards, quality control, and measurement sciences in 3D printing and additive manufacturing - Chua, Chee Kai; Wong, Chee How; Yeong, Wai Yee (Academic Press is an imprint of Elsevier, 2017)
"Standards, Quality Control and Measurement Sciences in 3D Printing and Additive Manufacturing addresses the critical elements of the standards and measurement sciences in 3D printing to help readers design and create safe, reliable products of high quality. With 3D printing revolutionizing the process of manufacturing in a wide range of products, the book takes key features into account, such as design and fabrication and the current state and future potentials and opportunities in the field. In addition, the book provides an in-depth analysis on the importance of standards and measurement sciences. With self-test exercises at the end of each chapter, readers can improve their ability to take up challenges and become proficient in a number of topics related to 3D printing, including software usage, materials specification and benchmarking. Helps the reader understand the quality framework tailored for 3D printing processesExplains data format and process control in 3D printingProvides an overview of different materials and characterization methodsCovers benchmarking and metrology for 3D printing"--